Air raid--Pearl Harbor! : the story of December 7, 1941 - Taylor, Theodore, 1921-2006. (New York : Scholastic, 1971)
Examines from both the American and Japanese points of view the political and military events leading up to the attack on Pearl Harbor.
Keywords: Pearl Harbor (Hawaii), Attack on, 1941 -- Juvenile literature; Pearl Harbor (Hawaii), Attack on, 1941.; World War, 1939-1945 -- Causes; Japan -- Foreign relations -- United States; United States -- Foreign relations -- Japan